A mechanistic explanation of two novel Zn(II) dithiocarbamate complexes with β-lactoglobulin. Issue 14 (22nd September 2021) - Shiri, Fereshteh; Shahraki, Somaye; Frozandeh-Moghadam, Hossein
Abstract: The synthesis, characterization, antioxidant activity and β-LG interaction of two Zn(II) complexes formulated as [(N-N)Zn(µ-pr-dtc)Zn(N-N)](NO3 )2 ] (where pr-dtc is propylenbisdithiocarbamate, N-N are 2, 2′-bipyridine for complex a, and 1, 10 phenanthroline for complex b ) were reported. The in vitro antioxidant activity of the Zn complexes was evaluated against 1, 1-diphenyl-2-picrylhydrazyl radicals (DPPH). Both complexes presented moderate antioxidant activity (IC50 = 231.0 ± 5.7 mg L −1 for complex a and 250.0 ± 6.1 mg L −1 for complex b ). Fluorescence studies showed that the intrinsic fluorescence of β-LG was statically quenched by the prepared complexes mainly through Van der Waals interaction and hydrogen bond. The fluorescence results showed that the above complexes could bind with β-LG with a relatively strong affinity (complex a: K b(27 °C) = 0.16 × 10 4 M −1, K b(37 °C) = 0.06 × 10 4 M −1, complex b: K b(27 °C) = 1.94 × 10 4 M −1, K b(37 °C) = 0.11 × 10 4 M −1 ). The secondary structure of β-LG was changed in the presence of these Zn complexes and the decrease in α-helix (0.41% and 0.55% for complex a and complex b, respectively) and β-sheet (1.19% and 1.44% for complex a and complex b, respectively) contents confirmed the protein instability during the interaction. Molecular dynamics simulation was used during the preparation of the protein receptor before docking to find the best fit of the complexes to β-LG. Some details about molecular docking simulations describe Van der Waals interactions and hydrogen bonding, and this is in agreement with the thermodynamics data derived from fluorescence spectroscopy experiment. Communicated by Ramaswamy H. Sarma